Natural heritage: updating the debate on identification and recognition within Iphan - Pereira, Danilo Celso (Revista CPC, 2018)
The public policies of Brazilian cultural heritage selection opted for the protection of certain goods over others, and in this dispute field the natural heritage has historically been presented as one of the least privileged categories. The objective of this paper is to discuss the policy of identification and recognition of natural heritage by the National Institute of Historical and Artistic Heritage, seeking to understand the natures considered relevants to be part of the mosaic that intends to represent the national identity. The present study is based on specialized literature review and on the analysis of the listing processes, making it possible to verify that the critical revision of the notion of cultural patrimony in the 1970s and 1980s allowed the recognition of new natural patrimonies, linked to the daily life and the memory of the different formative groups of Brazilian society, and nowadays it is noticeable a misunderstanding of the subject, when there is the intention of delegating the natural heritage to the legislation of the environment.